A Retrospective Study of Epidemiological Trends of Leprosy in An Urban Leprosy Centre Of Madhya Pradesh - Jain, Swati; Mishra, Mahesh Kumar; Gupta, Sanjay Kumar; Jain, Vikas; Balpande, Leena (National Journal of Community Medicine, 2014)
Introduction: Leprosy is a chronic infectious disease caused by Mycobacterium Leprae, affecting mainly peripheral nerves and skin. An impressive decline in leprosy prevalence rate (PR) in India is seen in the post-MDT era. This study was carried out to find out the trend of leprosy in urban leprosy center of Madhya Pradesh and to interpret this data with respect to different epidemiological variable. Methodology: This was a retrospective study conducted by analyzing records of Urban Leprosy Center, from Jan2004 to Dec 2013. Result: A total 304 patient attended ULC (Urban Leprosy Center) during last 10 years (2004-2013), among which 58.2% were male and 41.8% female. Analysis of data showed a gradual decline in new case detection till 2006 in this set-up with marginal rise observed in 2007, 2009 and 2012 when compared with previous years. However, majority of patient 173 (56.9%) belonged to multibacillary (MB) group while 131(43.1%) were paucibacillary (PB) cases. Prevalence of disability (both grade 1 and grade 2) was more in male than in female. Disability rate was more in multibacillary leprosy than in paucibacillary patient. Most common deformity among study subjects were claw hand (60%). Conclusion: To conclude while leprosy incidence has declined after MDT, early detection & proper monitoring of new cases was required to facilitate effective management, disability limitation and rehabilitation